Faktor klinis dan demografis yang memengaruhi outcome pascaoperasi pada pasien bedah - Xiong Cai; Wienaldi Wienaldi; Liena Liena (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Postoperative success is an important indicator of postoperative outcomes used to assess the quality of surgical care in hospitals. Factors related to the surgical procedure also play a role in determining postoperative outcomes. The type of surgery, the complexity of the procedure, and the duration of the surgery can influence the patient's physiological condition during and after surgery. Purpose: To analyze factors influencing postoperative outcomes in hospitalized patients. Method: This study used a quantitative observational approach with an analytical approach. The study was conducted on inpatients at Royal Prima Medan Hospital in 2025. Bivariate and multivariate analyses were applied to assess the relationship between variables. Results: Age, type of surgery, duration of surgery, and comorbidity status were significantly associated with postoperative outcomes (p < 0.05), while gender had no significant effect (p = 0.542). Patients aged ≤45 years and without comorbidities mostly experienced optimal recovery, while patients >45 years with comorbidities or undergoing emergency surgery tended to require further monitoring. Multivariate analysis confirmed comorbidity as the dominant factor increasing the risk of requiring further monitoring (OR = 3.78; 95% CI: 1.59–9.11; p = 0.003). Conclusion: The role of physiological reserve, surgical complexity, and comorbidities influence the postoperative recovery process.   Keywords: Age; Clinical Risk; Comorbid Status; Duration of Surgery; Postoperative Outcomes; Type Of Surgery.   Pendahuluan: Keberhasilan pascaoperasi merupakan salah satu indikator penting dari outcome pascaoperasi yang digunakan untuk menilai mutu pelayanan bedah di rumah sakit. Faktor yang berkaitan dengan tindakan pembedahan juga berperan dalam menentukan outcome pascaoperasi. Jenis operasi, tingkat kompleksitas tindakan, serta lama operasi dapat memengaruhi kondisi fisiologis pasien selama dan setelah pembedahan. Tujuan: Untuk menganalisis faktor-faktor yang memengaruhi outcome pascaoperasi pada pasien rawat inap. Metode: Jenis penelitian yang digunakan adalah observasional kuantitatif dengan pendekatan analitik yang dilakukan kepada pasien rawat inap di RSU Royal Prima Medan tahun 2025. Analisis bivariat dan multivariat diterapkan untuk menilai hubungan antarvariabel. Hasil: Usia, jenis operasi, lama operasi, dan status komorbid berhubungan signifikan dengan outcome pascaoperasi (p < 0.05), sedangkan jenis kelamin tidak berpengaruh signifikan (p = 0.542). Pasien usia ≤45 tahun dan tanpa komorbid mayoritas mengalami pemulihan optimal, sementara pasien >45 tahun dengan komorbid, atau menjalani operasi emergensi cenderung memerlukan pemantauan lanjutan. Analisis multivariat menegaskan status komorbid sebagai faktor dominan yang meningkatkan risiko perlunya pemantauan lanjutan (OR = 3.78; 95% CI: 1.59–9.11; p = 0.003). Simpulan: Peran cadangan fisiologis, kompleksitas operasi, dan kondisi medis penyerta memengaruhi proses pemulihan pascaoperasi.   Kata Kunci: Jenis Operasi; Lama Operasi; Outcome Pascaoperasi; Risiko Klinis; Status Komorbid; Usia.